2018
DOI: 10.1002/ijgo.12597
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalization of postpartum intrauterine devices

Abstract: Globally, 225 million women need contraception. Birth spacing reduces perinatal and maternal morbidity and mortality. PPIUD is cost‐effective and reversible with minimal expulsions and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…During the first year postpartum, 40% of 3 women are estimated to have an unmet need for contraception (7). Closely spaced pregnancies give rise to adverse maternal, perinatal and infant outcomes (8). The PPIUD enables women to leave the birth facility with a safe and extremely effective LARC ready in place (15).…”
Section: Postpartum Family Planningmentioning
confidence: 99%
“…During the first year postpartum, 40% of 3 women are estimated to have an unmet need for contraception (7). Closely spaced pregnancies give rise to adverse maternal, perinatal and infant outcomes (8). The PPIUD enables women to leave the birth facility with a safe and extremely effective LARC ready in place (15).…”
Section: Postpartum Family Planningmentioning
confidence: 99%
“…In Nepal, PPIUD is currently the only reversible PPFP method available in the immediate post-partum period. Despite the advantages of PPFP, the use of immediate PPFP methods such as PPIUD remains low in Nepal as compared to other countries [10]. A qualitative study from the earlier phase of implementation of this initiative identified societal norms, as well as peer and health provider influences as factors that affected women's behavior on choosing a PPFP method [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nepal Society of Obstetricians and Gynecologists (NESOG) jointly with the Nepalese government and with the support from International Federation of Obstetrics and Gynecology (FIGO) had implemented the initiative of institutionalizing immediate postpartum family planning (PPFP) services in selected major referral facilities of Nepal between 2015 and 2019. [1][2][3] The initiative had focused on PPFP services that could be incorporated as a routine part of maternity care in the selected hospitals. The outcome of institutionalization was to improve the coverage of PPFP counseling and uptake of immediate PPFP methods.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of institutionalization was to improve the coverage of PPFP counseling and uptake of immediate PPFP methods. [1][2][3] The increasing institutional deliveries in Nepal provides a one-stop approach to provide maternity and PPFP service at the same time. 4 However, the data on postpartum family planning service coverage from the health facilities in Nepal remains limited.…”
Section: Introductionmentioning
confidence: 99%